Validation of the Karasek-Job Content Questionnaire to Measure Job Strain in Vietnam. Issue 2 (October 2013) - Hoang, Thi Giang; Corbière, Marc; Negrini, Alessia; Pham, Minh Khuê; Reinharz, Daniel
The objective of this study was to validate the Karasek-Job Content Questionnaire in Vietnamese. A translation/back-translation of the questionnaire was performed prior to its administration to 344 health personnel in Vietnam. Several psychometric properties of the Vietnamese version of the Karasek-Job Content Questionnaire were assessed. A valid Vietnamese version of the Karasek-Job Content Questionnaire was produced, composed of five subscales based on the original theoretical model: Psychological demands, Social support at work, Decision latitude-Autonomy, Decision latitude—Authority, and Skill discretion. Internal consistency and reliability coefficients for each subscale of the questionnaire were satisfactory. The correlations with depression and work absence indicators were weak but statistically significant, as expected. The Vietnamese version of the Karasek-Job Content Questionnaire will help Vietnamese researchers and clinicians appropriately evaluate and document the job strain of workers in Vietnamese workplaces.